The Study of Supply Chain strategy, Educational Basicals, Community Perceptions on Several Hindu Sampradaya at Singaraja Town, Bali - I Wayan Suwendra (International Journal of Supply Chain Management, 2019)
This research was conducted because of it was not known about the meditation system, educational fondations and Balinese Hindu perception toward the sampradaya at Singaraja town the Bali of Province, namely: Sai StudyGroup (SSG), Krsna Conciousnese (KC), Ananda Marga (AM), Brahma Kumaris, Sapta Dharma and so on. This research was focus to 3 sampradayas, such as: SSG, KC and AM. The purposes of the study were been knowing meditation system, educational fondations and Balinese Hindu perceptions to the sampradayas existance. The basically theories were used in studying these problems were kundalini theory, educational theory and social perception theory. This research was applied qualitative approarch by analysing steps such as: data collecting, data displying, data reducting and data verificating or making conclussion. The result of this research, the SSG have more variative meditation then the others. SSGâ€™s opinion is the most effective meditation on Kaliyuga era is namasmaranam meditation. Three sampradayas have simillar were freedom or mokhsa. The basically of educational fondations is still in Panca Craddha frame. SSG are empazising on Panca Pilar (dharma, sathya, prema, santhi and ahimsa), changing the human beeing into Deva or Devi personality, and education of SSG are much more toward to inside of human beeing (Atman conciousnese). The basic of education Krsna conciousnese are Bhagavadgita and Purana Bhagavatham. The other hands, Ananda Marga is using â€œNeo Humanismâ€ as the basic of his education. Balinese Hindu perceptions toward to three sampradayas were positive, (75 %) neutral (20%) and negative perceptions (5%) in difference parts, depending on education, economical, social degrees or stratification. All of sampradayas (three sampradayas) were still in Hindu frame and base on Catur Veda Manuscripts there fore the Hindu people can be more tolerant, appreciate, cooperative to each other.